Unemployment Normalization: Its Effect on Mental Health During Various Stages of Unemployment. Issue 5 (October 2019) - Thill, Steve; Houssemand, Claude; Pignault, Anne
The negative effects of job loss on mental health have been thoroughly described in the literature. However, different fluctuations in mental health during the unemployment period have been noticed. We argue that a coping process takes place in this kind of situation. Therefore, in this study, we investigated the effect of the unemployment normalization process on mental health during various stages of unemployment. Participants ( N = 803) completed the General Health Questionaire-12 and the Unemployment Normalization Questionnaire. Results showed that a negative perception of unemployment had the greatest impact on mental health during the different phases of unemployment. Nevertheless, during the first year, having a positive perception counteracted these negative effects, and after 1 year, the unemployment norm took over the role of buffering against the negative effects on mental health. These results indicate that unemployment is still perceived as negative, but depending on the stage of unemployment, various coping strategies are used to buffer the negative consequences of unemployment.